2015
DOI: 10.1515/znb-2015-0062
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated 9,10-dihydrophenanthrenes from Macaranga javanica

Abstract: Phytochemical investigation of the acetone extract of Macaranga javanica leaves afforded three new prenylated 9,10-dihydrophenanthrenes, macajavanicins A-C (1-3). Structures of these compounds were elucidated mainly by NMR and mass spectral data. Along with compounds 1-3, two known prenylated dihydrostilenes, laevifolins A and B (4, 5), were also isolated. The presence of these new 9,10-dihydrophentanthrene derivatives is the first time in the genus Macaranga, and its chemo taxonomic significances are briefly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Prenyl-substituted phenanthrenes are relatively uncommon. However, Ilmiawati et al reported five prenylated compounds, including three new prenyl-substituted phenanthrenes ( 62 , 63 , 161 ) from Macaranga javanica (Euphorbiaceae) …”
Section: Compound Structural Diversity and Biological Activitymentioning
confidence: 99%
“…Prenyl-substituted phenanthrenes are relatively uncommon. However, Ilmiawati et al reported five prenylated compounds, including three new prenyl-substituted phenanthrenes ( 62 , 63 , 161 ) from Macaranga javanica (Euphorbiaceae) …”
Section: Compound Structural Diversity and Biological Activitymentioning
confidence: 99%
“…5). The antibacterial assay on laevifolins A (1) and B (2) on S.aureus (clinical isolate) have been reported before by Ilmiawati and co-workers [14] with MIC values 35 As for cytotoxicity, laevifolin A (1) displayed pronounced inhibition on HT-29 cells with an IC 50 value of but no IC 50 observed in laevifolin B (2). The steric hindrance enhanced the activity due to the accessibility of laevifolin A (1) to exert its effect on the cancer cells [21].…”
Section: Resultsmentioning
confidence: 55%
“…As for the biological activities, laevifolins A (1) and B (2) were reported for their antibacterial activity (Bacillus subtilis, Enterobacter aerogenes, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Shigella dysenteriae, Staphylococcus aureus, and Vibrio cholera) and cytotoxicity of murine leukemia (P-388 cells). Meanwhile, macarubiginosin C (3) was only tested on P-388 cells [14,20]. In this study, the compounds were assayed on different bacteria and cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, flavonoids displayed significant role in dietary antioxidant by reducing the oxidative stress in the body [15]. Meanwhile, the stilbenoids namely laevifolins A and B which were isolated from M. javanica possessed significant activities against S. aureus with MIC values 35 μM [16].…”
Section: Introductionmentioning
confidence: 99%